Evaluasi Usability Pada Sistem Informasi Beasiswa Menggunakan Metode Heuristic Evaluation dan Think Aloud - Riska Ayuni; Tengku Khairil Ahsyar; Muhammad Luthfi Hamzah (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
The scholarship information system needs to cover several aspects so that it can always maintain the superior quality of use and existing information, one of which is the usability aspect. Based on initial observations that have been made on the information system, there is user dissatisfaction such as sometimes errors when inputting data by staff, inconsistencies in some displays, no menu for forgotten password, no contact information, no help menu, parts of the site interface are difficult to understand. . The problem is related to usability. Usability evaluation is carried out to evaluate the system based on the level of effectiveness, efficiency and satisfaction. The purpose of this research was to evaluate the ease of use of the UIN Suska Riau Scholarship information system. The purpose of this evaluation is to see how easy the system is to use and to make recommendations about possible improvements. Data collection through observation, interviews, and questionnaires. in the heuristic evaluation method the data analysis method used is usability testing, and the data processing tool used is Statistical Product Solution (SPSS) Statistics 23 software from IMB Software. and 8 to 10 respondents for Think Aloud. For the evaluation of this study, two approaches were used, Heuristic Evaluation and Think Aloud. Heuristic Evaluation is used to evaluate the interface using a heuristic questionnaire, while Think Aloud is used to evaluate the use of the information system based on what the user says. At the Think Aloud data collection stage, each participant will carry out a task scenario to provide criticism or reveal the problems they are experiencing. The results of the data analysis succeeded in identifying identified gaps in the information system assessed in this study and providing recommendations for improvement. The results of the Heuristic Evaluation Analysis show that this system obtains a percentage score of 75%, which indicates a sufficient level of goodness for its users. However, there is a total of 25% where deficiencies are found in the system, it shows that this system is not good for its users. Then, through Think Aloud analysis, found up to 23 suggestions for improvement for the system being evaluated. Future research can further evaluate the implementation of these improvement recommendations